Management of Work-Based Competency Testing at Vocational Schools for Light Vehicle Body Engineering - Dadan Budiman; Emay Mastiani (Journal of General Education and Humanities, 2026)
Work-Based Competency Testing (Uji Kompetensi Keahlian/UKK) plays a strategic role in ensuring the competence and quality of vocational high school (SMK) graduates. However, the implementation of UKK in Light Vehicle Body Engineering programs often faces challenges, particularly the limited and suboptimal involvement of the world of work, which reduces the relevance of competency standards to industry needs. This study aims to analyze the management of work-based competency testing in vocational schools and to examine how industry involvement is integrated into each management stage. This research employed a qualitative approach using a case study design conducted at SMKN 8 Bandung and SMKN 14 Bandung. Data were collected through in-depth interviews, direct observations, and documentation studies. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that work-based UKK management is systematically implemented through the stages of planning, organizing, implementing, and evaluating, with active participation from industry partners. Industry involvement from the initial planning phase to the final evaluation stage enhances the alignment between competency testing and industry standards, increases the credibility of the certification process, and contributes to improving graduate quality. The study concludes that effective work-based competency test management strengthens the link and match between vocational education and industry demands.